Foreign students adaptation management, assessment and forecasting algorithms and software; Advances in Computer Science Research; Vol. 72 : Information technologies in Science, Management, Social sphere and Medicine (ITSMSSM 2017) - Romanchukov S. Sergey; Fisochenko O. N. Oksana Nikolaevna; Berestneva O. G. Olga Grigorievna; Sharopin K. Konstantin (2017, 2017)
Title screen